2014
DOI: 10.1103/physrevb.89.125411
|View full text |Cite
|
Sign up to set email alerts
|

Exotic fractional topological states in a two-dimensional organometallic material

Abstract: Fractional Chern insulators (FCIs), having properties similar to those of the fractional quantum Hall effect, have been established numerically in various toy models. To fully explore their fundamental physics and to develop practical applications, material realization is indispensable. Here we theoretically predict a realization of FCI in a two-dimensional organometallic material, which is known to have the prerequisite topological flat bands. Using numerical exact diagonalization we demonstrate that the pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
0
22
1
Order By: Relevance
“…To see this competition quantitatively, let us calculate an example [52]. We will consider the XYH lattice.…”
Section: Phase Diagram: a Case Studymentioning
confidence: 99%
“…To see this competition quantitatively, let us calculate an example [52]. We will consider the XYH lattice.…”
Section: Phase Diagram: a Case Studymentioning
confidence: 99%
“…Here, we first calculate the static structure factor with charge and spin degrees of freedom 21 : Ψ|n(Ŝ) j |Ψ Ψ|n(Ŝ) l |Ψ ) , whereŜ i = 1 2 (n i↑ −n i↓ ) is a spin operator, and the wave function |Ψ is incoherent summation over the degenerate ground states, shown in Fig. 3(c).…”
Section: Fillingmentioning
confidence: 99%
“…Recently, a series of flat-band lattice models with nonzero Chern number, which belong to the same topological class as the Haldane lattice model, have been proposed [10][11][12] and demonstrated to host the fractional Chern insulating phases [12][13][14][15][16][17][18][19][20][21] when interacting particles partially fill up these topological flat bands. Such topological nontrivial states are examples of the fractional quantum Hall (FQH) effect without an external magnetic field.…”
mentioning
confidence: 99%
“…Moreover, it was found that the charge ordering can coexist with topological ordering [73,75]. However, contrary to the Landau levels in which the Wigner crystallization occurs at arbitrarily low fillings, the short-range nature of interaction considered in [69][70][71][72][73][74][75] limits this effect to a certain filling factor.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors investigated the charge ordering induced by short-range interaction at high filling factors [69][70][71][72][73][74][75]. Phase diagrams of various flat band models were obtained, showing the competition between the FCI and chargeordered ground state [71][72][73][74]. Moreover, it was found that the charge ordering can coexist with topological ordering [73,75].…”
Section: Introductionmentioning
confidence: 99%